Communicating About Water in the Floridan Aquifer Region: Part 6—Stakeholders’ Mental Models of Regional Water Challenges - Sadie Hundemer; Shenara Ramadan (EDIS)
If we could look into the minds of agricultural producers and environmentalists to see how they think about regional water challenges, we may be better able to help stakeholders understand each other’s perspectives and resolve perceived conflicts. A 2017–2018 study provides visual maps of producers’ and environmentalists’ conceptions of the relationship between water and the regional economy. The maps reveal that the groups think about the topic in fundamentally different ways. While surveyed producers possess an agricultural, operational-level view of the water-economic system that includes the protective actions taken by individual farmers and ranchers, environmentalists possess a watershed-level view of the water-economic system that highlights the detrimental collective impacts of the agricultural industry as a whole. The findings suggest steps that water communicators can take to reduce perceived conflict between the groups.